2020
DOI: 10.1111/1755-6724.14306
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Influence of Pore Structure on Resistivity, Formation Factor and Cementation Index in Tight Sandstone

Abstract: Tight sandstone, with severe diagenesis and complex pore structure, differs greatly from conventional sandstone in terms of rock electrical parameters. In subsurface rock electrical experiments, various electrical parameters are confounded and can only be analyzed qualitatively. The lack of quantitative analysis for each individual electrical parameter presents a challenge for the evaluation of oil and gas saturation in tight sandstone. Based on the 2D pore‐throat model and the features of pore structure in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In tight gas reservoirs in the Xujiahe Formation in the Western Sichuan Depression, nanoscale pore throats often take the form of sheets or bent sheets, with their formation primarily linked to compaction during diagenesis [29,36,38,41,49]. Studies comparing pore throat development in the T 3 x 2 and T 3 x 4 sections have suggested that the latter exhibits a greater number of throats, with larger throat radii.…”
Section: Pore Structure Characteristicsmentioning
confidence: 99%
“…In tight gas reservoirs in the Xujiahe Formation in the Western Sichuan Depression, nanoscale pore throats often take the form of sheets or bent sheets, with their formation primarily linked to compaction during diagenesis [29,36,38,41,49]. Studies comparing pore throat development in the T 3 x 2 and T 3 x 4 sections have suggested that the latter exhibits a greater number of throats, with larger throat radii.…”
Section: Pore Structure Characteristicsmentioning
confidence: 99%
“…The western Sichuan depression entered the foreland basin development stage from the end of the Late Triassic and deposited a thick Triassic-Jurassic-Cretaceous terrigenous clastic strata. A large number of tight gas reservoirs have been found in the Triassic Xujiahe Formation, the Shaximiao Formation and the Penglaizhen Formation in the Jurassic [38]. The study area of this research is the Majing-Shifang-Xinchang contiguous structure and the object of the study is the tight sandstone reservoirs of the Shaximiao Formation and the Penglaizhen Formation in the Jurassic (Figure 5).…”
Section: Gas-water Two-phase Flow Simulationmentioning
confidence: 99%
“…During the drilling fluid cycle, the drilling fluid infiltrates the formation rock through pores, thus blocking the pores in rock (Figure 1b,c) and reducing the permeability of the formation, resulting in a dramatic decline in oil and gas recovery efficiency [5][6][7]. In low-porosity and low-permeability sandstone reservoirs [8][9][10][11][12], the formation damage from drilling fluid is extremely complicated. Therefore, with the gradual advancement of exploration and the development of low-porosity and low-permeability sandstone reservoirs, the study of the microscopic mechanism of formation damage by drilling fluid has received increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%